Age Related Histological and Histochemical Studies on the Gizzard of Broiler Chickens - Mehra, Asha (Indian Journal of Veterinary Anatomy, 2020)
Gizzard was characterized by an internal abrasion-resistance lining koilin, glycoprotein in nature, showed different affinity for PAS and thick muscular layer. The mucosa present in the form folds and was lined by simple columnar epithelium. The lamina muscularis mucosae was absent. The mucosal epithelium lining of the surface and gastric pits of glands indicated the presence of both neutral and acidic mucopolysaccharides. The propriasubmucosa was having loose irregular connective tissue. The number of cell layers in different strata, concentration of glands and thickness of the muscle layers increased with advancement of age.